2019
DOI: 10.1111/1348-0421.12664
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of enzyme immunoassay that detects rubella‐specific immunoglobulin M immediately after disease onset

Abstract: A total of 300 patients with nucleic acid test-confirmed rubella, mostly adults, were investigated to determine the clinical value of a rubella-specific IgM test using an EIA kit. IgM titers increased after rash onset, the median IgM titer being significantly higher 3 days post-onset than on previous days (P < 0.0001). Similarly, the IgMpositive rate at 3 days post-onset (61.5%) was significantly higher than on previous days (P < 0.0001). This IgM test against rubella at 3 days or more post-disease onset provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The possibility of misclassification of false-positive rubella IgM was thought to be low. Moreover, previous reports showed that this rubella-specific IgM test (EIA kit) indicated highly positive results for rubella (reaching 80%) among patients who received this test after 5 days of the onset of symptoms [27]. Therefore, we conducted the multivariate analysis between 33 AR and 72 ANR who were diagnosed after 5 days of onset of symptoms or confirmed by RT-PCR.…”
Section: Discussionmentioning
confidence: 97%
“…The possibility of misclassification of false-positive rubella IgM was thought to be low. Moreover, previous reports showed that this rubella-specific IgM test (EIA kit) indicated highly positive results for rubella (reaching 80%) among patients who received this test after 5 days of the onset of symptoms [27]. Therefore, we conducted the multivariate analysis between 33 AR and 72 ANR who were diagnosed after 5 days of onset of symptoms or confirmed by RT-PCR.…”
Section: Discussionmentioning
confidence: 97%